Pleiotropic effects of SGLT2 inhibitors and heart failure outcomes. (June 2022) - Theofilis, Panagiotis; Sagris, Marios; Oikonomou, Evangelos; Antonopoulos, Alexios S.; Siasos, Gerasimos; Tsioufis, Kostas; Tousoulis, Dimitris
Graphical abstract: The pleiotropic effects of SGLT2 inhibition leading to the reduction in hospitalization and improvement of quality of life in heart failure (HF) patients. SGLT2 inhibitors act through antioxidant (yellow), anti-inflammatory (orange), and anti-fibrotic (purple) pathways, while also promoting autophagy (blue) in cardiomyocytes. Moreover, they ameliorate endothelial function of cardiac microvascular endothelial cells (CMEC) by improving nitric oxide (NO) bioavailability. Additionally, they aid epicardial adipose tissue (EAT, red) shrinking by downregulating leptin. Ultimately, reversal of adverse cardiac remodeling is being observed, leading to a reduction in HF hospitalizations and improvement of quality of life. eNOS: endothelial NO synthase, PKG: protein kinase G, NOX: NADPH oxidase, THB: tetrahydrobiopterin, ROS: reactive oxygen species, NLRP3-I: NLRP3 inflammasome, NF-κB: nuclear factor kappaB, TGF: transforming growth factor, AMPK: AMP-activated protein kinase, ER: endoplasmic reticulum, Abstract: Heart failure (HF) represents a major public health concern with increasing prevalence among aging populations, with multifactorial pathophysiology including inflammation, oxidative stress, endothelial dysfunction, and fibrosis, among others. Lately, the use of sodium-glucose cotransporter-2 (SGLT2) inhibitors, originally destined for the treatment of type 2 diabetes mellitus, have revolutionized the treatment of HF. In this review article, we provide the milestones and the latest mechanistic evidence of SGLT2 inhibition in HF. Owing to the results of experimental studies, several pleiotropic effects of SGLT2 inhibitors have been proposed, including the restoration of autophagy which may be significant in the reversal of the aforementioned HF pathophysiology according to a latest hypotheses. Additional mechanisms consist of the regulation of inflammatory, oxidative, and fibrotic pathways, together with the improvement of endothelial function and reduction of epicardial adipose tissue. Other than their role as antidiabetic agents, a reduction in heart failure hospitalizations has been noted following their use in clinical trials, irrespective of DM status and degree of systolic dysfunction. Upcoming randomized trials are expected to additional clinical and mechanistic evidence regarding the diverse effects of SGLT2 inhibition across the spectrum of heart failure.